ANALISIS LAPORAN ARUS KAS SEBAGAI EVALUASI KINERJA PERUSAHAAN PADA PT. MAYORA INDAH TBK - B51107138, Aulia Rahmat (Jurnal KIAFE, 2013)
Cash flow statement is a report that provides information about the cash inflows and outflows during the period that shows the source of cash generated and for any use, including information on the activities and financing uses of cash from the company for a certain period. Cash flow statement also describes changes in cash balances. Therefore, the analysis of the cash flow statement is needed to refine the results of the evaluation of a company's financial performance. Issues raised in this paper is how the company PT Mayora Indah Tbk measure of the cash flow statement, and what factors are influential in supporting the evaluation of the performance of the company in managing the company's cash flow. PT Mayora Indah Tbk is a company engaged in the processed food and beverage industry. PT Mayora Indah Tbk classifies cash flows into three activities, namely operating, investing and financing activities. The analysis carried out on the cash flow statement Mayora Indah Tbk PT is using a ratio based on cash flow analysis. The analysis is done by comparing the ratio of the figures contained in the 2008 financial year to 2011 so as to know the financial condition of the company if the terms of its cash flow. Ratio analysis covered include ratio analysis, liquidity, solvency, capital expenditures, investments and cash flow return ratio. Based on the analysis conducted, it can be concluded that the efficiency and effectiveness of the company from 2008 to 2009 has increased, but decreased in 2010 and 2011 also experienced a drop in a pretty drastic. Mayora Indah Tbk PT should have a more competitive by improving cost efficiency and should increase the company's investment activities, such as ownership by buying other companies that have the potential to increase corporate profits.